1988
DOI: 10.1007/bf01075989
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and recovery contractile properties of young and elderly men

Abstract: The 24 h recovery pattern of contractile properties of the triceps surae muscle, following a period of muscle fatigue, was compared in physically active young (25 years, n = 10) and elderly (66 years, n = 7) men. The fatigue test protocol consisted of 10 min of intermittent submaximal 20 Hz tetani. The maximal twitch (Pt) and tetanic force at 3 frequencies (10, 20 and 50 Hz) were determined at baseline and at 15 min, 1, 4 and 24 h after fatiguing the muscle. Maximal voluntary contraction (MVC) and vertical jum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
41
1
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 31 publications
6
41
1
1
Order By: Relevance
“…The delayed force recovery of skeletal muscle that has been observed in aging animals is concordant with the findings of several earlier studies in humans (Dedrick & Clarkson, 1990;Klein et al, 1988). Dedrick and Clarkson found that lengthening contractions in college-age women (23.6 ± 3.3 years) elicited the greatest strength loss immediately after the exercise, and thereafter strength demonstrated a progressive return to preexercise values after 3 days.…”
Section: Repair and Adaptation Of Skeletal Musclesupporting
confidence: 78%
See 2 more Smart Citations
“…The delayed force recovery of skeletal muscle that has been observed in aging animals is concordant with the findings of several earlier studies in humans (Dedrick & Clarkson, 1990;Klein et al, 1988). Dedrick and Clarkson found that lengthening contractions in college-age women (23.6 ± 3.3 years) elicited the greatest strength loss immediately after the exercise, and thereafter strength demonstrated a progressive return to preexercise values after 3 days.…”
Section: Repair and Adaptation Of Skeletal Musclesupporting
confidence: 78%
“…Using a fatiguing but not necessarily damaging exercise protocol in humans, Klein et al (1988) found there were no significant differences between young (19-32 years) and older (64-69 years) adults for loss of force during a fatigue test or the recovery of force during 1 hr of recovery in the triceps surae muscle. These researchers, however, reported that in the older participants there was a decrease in the rate of relaxation of twitch force and an increased half-relaxation time.…”
Section: Repair and Adaptation Of Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation
“…Results have been reported for both voluntary and electrically elicited contractions, but there are discrepancies among the published studies and comparison is difficult as different measures of fatigue have been used and different muscles have been investigated. Some investigators have reported higher fatigability in elderly subjects during electrically elicited contractions, 9,31 others found lower fatigability, 44 and others found no age-related change in muscle fatigability 23,41 or endurance during voluntary contractions. 30, 45 Merletti et al 41 found, with voluntary contractions of the tibialis anterior muscle, a lower level of myoelectric manifestations of muscle fatigue in a group of elderly subjects compared to a control group of young subjects.…”
mentioning
confidence: 99%
“…46 In general, low-frequency stimulation (20 Hz) induces greater fatigue in older compared to younger adults, 16,17,40 whereas fatigue rates are similar during evoked contractions with higher frequencies (40 Hz) of stimulation. 16,36,44 It is not known whether muscles paralyzed by stroke in older adults would show the same responses to variable patterns of stimulation as those of young adults paralyzed by SCI.…”
mentioning
confidence: 95%